Prediction and analysis of thermal-hydraulic performance with slit fins in small diameter (3 mm to 4 mm) heat exchangers. (December 2021) - Zhi, Changshuang; Du, Shunkai; Zhao, Fufeng; Li, Jinbo; Liu, Yingwen
Abstract: The simulation model describes the thermal-hydraulic performance and is verified well by comparing with the experimental data. The 122 runs taking 7 geometric parameters and Reynolds number into account are carried out based on the Response Surface Methodology (RSM). The correlations of the heat transfer ( j -factor) and flow friction ( f -factor and Eu -number) in 3 mm diameter are proposed. The mean deviations of the correlations with j -factor, f -factor and Eu -number are 3.78%, 2.56% and 2.51% respectively. The effects of 7 geometric parameters are investigated using the RSM model in detail at Re  = 500, and it can be found that the height of the slit ( Sh ) has the greatest influence on j -factor. The differences in the change rate of f -factor and Eu -number are emphatically analyzed. And the effects of the transverse tube pitch ( Pt ) on f -factor and Eu -number are opposite. The f -factor is positively correlated with Pt, while the Eu -number is negatively correlated with Pt . In addition, the coefficients of correction for j -factor, f -factor and Eu -number are obtained to make available for different collar diameters. In the range of 3.19–4.19 mm collar diameter, the mean deviations of the modified correlations including j -factor, f -factor and Eu -number are 6.24%, 5.46%, and 4.26% respectively. Highlights: Correlations of j, f and Eu factors are proposed in 3 mm diameter heat exchangers. The effects of 7 geometric parameters are investigated using the RSM model. The height of the slit ( Sh ) has the greatest influence on j -factor. The effects of the transverse tube pitch ( Pt ) on f -factor and Eu -number are opposite. The modified correlations are obtained for 3.19 mm–4.19 mm collar diameters.